2022
DOI: 10.1109/ojits.2022.3166394
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of the Impacts of the Time Headway of Adaptive Cruise Control Systems on Congested Urban Freeways Using Different Car Following Models and Early Control Results

Abstract: The impact of driving automation and adaptive cruise control (ACC) on traffic performance has been increasingly studied in recent years. This paper focuses on two widely used ACC car following models and investigates the impact of the time headway parameter on traffic operation and performance on one of the busiest freeway corridors in Ontario, Canada. Using Aimsun microsimulation, we compare two commonly used ACC car following models; the intelligent driver model (IDM) and Shladover's model which has been rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In our previous work, we demonstrated that in light traffic we could allow headways to be chosen by the driver, even if their choice was a long headway, because the impact on traffic was insignificant ( 5 ). However, in denser traffic, a simple on-off headway control strategy was demonstrated to improve freeway traffic performance significantly and transform the significant deterioration caused by adopting conservative headway settings into improvements by implementing the proposed control strategy ( 5 ).…”
Section: Experiments Setupmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work, we demonstrated that in light traffic we could allow headways to be chosen by the driver, even if their choice was a long headway, because the impact on traffic was insignificant ( 5 ). However, in denser traffic, a simple on-off headway control strategy was demonstrated to improve freeway traffic performance significantly and transform the significant deterioration caused by adopting conservative headway settings into improvements by implementing the proposed control strategy ( 5 ).…”
Section: Experiments Setupmentioning
confidence: 99%
“…According to ACC literature (2)(3)(4)(5), such systems have the potential to improve transportation network performance. However, if conservative values are set for ACC parameters (e.g., accelerations, headways) for comfort and safety reasons, deterioration in the transportation network performance is likely to happen.…”
mentioning
confidence: 99%
See 3 more Smart Citations